Policing sex - Johnson, Paul (Paul James); Dalton, Derek (New York : Routledge, 2012)
'This collection focuses attention on an important but academically neglected area of contemporary operational policing: the regulation of consensual sexual practices. Despite the high-level public visibility of, and debate about, policing in relation to violent and abusive sexual crimes (from child sexual abuse to adult rape) very little public or scholarly attention is paid to the policing of consensual sexual practices in contemporary societies. In the context of social and cultural change'sexual life' is largely understood as a matter of'private life,' policing plays an active part in regulating consensual sexual practices across a number of areas.This book brings together a well known and respected group of academics to explore the role of the police in shaping the boundaries of that aspect of contemporary life that we imagine to be most private and most our own, uniting scholars from a range of disciplines. It is essential supplementary readings for courses in criminology, law, policing, sociology of deviance, gender and sexuality, and cultural studies.'--
Includes bibliographical references and index.
Keywords: Sex -- Social aspects; Social control; Vice control